Evaluation of the Implementation of GeoGebra-assisted Advanced Calculus Courses Using the CIPP Model - Kelly Angelly Hevardani; Ambiyar; Yerizon; Yarman (Department of Mathematics, Universitas Negeri Padang (UNP), 2025)
This study aims to evaluate the implementation of advanced calculus courses assisted by GeoGebra using the CIPP model. This evaluation assessed the relevance, effectiveness, and results of applying GeoGebra as an interactive learning medium. The research approach was descriptive quantitative, with data collection through questionnaires and observations. The research subjects were 36 students who attended advanced calculus courses at FMIPA Universitas Negeri Padang in the July–December 2024 semester. The evaluation results show that in the context aspect, the use of GeoGebra is aligned with the curriculum objectives that support the mastery of advanced mathematical concepts and visualization skills. Regarding input, lecturers have basic competence in using GeoGebra, but not all students are familiar with this software. In terms of process, GeoGebra-assisted learning is interactive, although it is constrained by students’ adaptation time to the software. In terms of product, the evaluation results showed increased students’ analytical skills and conceptual understanding, although the increase in exam results was not significant overall. The findings recommend the need for intensive training for lecturers and students related to the use of GeoGebra, the provision of technology-based learning guides, and adjustments to lecture strategies to maximize the effectiveness of GeoGebra in supporting advanced calculus lectures.